2019
DOI: 10.1016/j.dib.2019.103836
|View full text |Cite
|
Sign up to set email alerts
|

A dataset of attributes from papers of a machine learning conference

Abstract: In this work, we present a dataset which provides information on the scientific program of a set conferences of Machine Learning. Data were extracted from the IEEE Xplore Digital Library and the official web site of the International Conference on Machine Learning Applications (ICMLA). We include data of four different editions (from 2014 to 2017). Web scrapping techniques were used to mine the data contained in these web sites. The dataset covers 448 papers presented in the conference and every paper contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The expansion of educational access via online platforms, as highlighted in this study, aligns with the findings of (Ifenthaler & Hofhues, 2021;Vallejo-Huanga et al, 2019), who noted the transformative role of digital learning in democratizing education. This is particularly relevant in Indonesia, where geographical and logistical barriers have traditionally limited access to continuing education.…”
Section: Discussionsupporting
confidence: 90%
“…The expansion of educational access via online platforms, as highlighted in this study, aligns with the findings of (Ifenthaler & Hofhues, 2021;Vallejo-Huanga et al, 2019), who noted the transformative role of digital learning in democratizing education. This is particularly relevant in Indonesia, where geographical and logistical barriers have traditionally limited access to continuing education.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the hypothesis test can be concluded that there are differences in the effectiveness of the Problem Based Learning and Study Team Achievement Division learning models on student achievement in 5th grade thematic learning of elementary school. The success of this research is supported by the increase in the results of the prettest to the posttest, so it can be seen that there is a significant difference (Castaneda et al, 2018;Hoffmann et al, 2022;Vallejo-Huanga et al, 2019). When the Problem Based Learning model has been implemented and the Study Team Achievement Division learning model has been implemented.…”
Section: Discussionmentioning
confidence: 73%
“…This expansion is particularly beneficial in Indonesia, where geographical and infrastructural challenges have historically limited access to such opportunities. The flexibility and convenience offered by these platforms have been crucial in enabling professionals to balance their ongoing education with work and personal commitments (Ifenthaler & Hofhues, 2021;Vallejo-Huanga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%